Untitled - Lawanson, Taibat; Eleshin, Abisoye (Lagos Ownership and Identities (Intellectual Debates and One Month Photography Exhibition), 2021)
Interview from respondents on Lagos history
Keywords: History; Migration; African Studies; Lagos; Knowledge